2016
DOI: 10.1016/j.brainres.2016.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde optogenetic characterization of the pontospinal module of the locus coeruleus with a canine adenoviral vector

Abstract: Noradrenergic neurons of the brainstem extend projections throughout the neuraxis to modulate a wide range of processes including attention, arousal, autonomic control and sensory processing. A spinal projection from the locus coeruleus (LC) is thought to regulate nociceptive processing. To characterize and selectively manipulate the pontospinal noradrenergic neurons in rats, we implemented a retrograde targeting strategy using a canine adenoviral vector to express channelrhodopsin2 (CAV2-PRS-ChR2-mCherry). LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
136
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(154 citation statements)
references
References 49 publications
(88 reference statements)
18
136
0
Order By: Relevance
“…We first examined if activation of the LC-NE neurons using electrical microstimulation would alter cortical arousal by shifting the power spectrum of cortical EEG, as had been previously shown using pharmacological compounds (Berridge and Foote, 1991; Steriade et al, 1993; Vazey and Aston-Jones, 2014) and photostimulation (Li et al, 2016). Consistent with previous work, brief electrical microstimulation (50 Hz, 6 biphasic current pulses, 200 ”s per phase, 60 or 120 ”A amplitude) of the LC induced the EEG power spectrum to shift towards higher frequencies (Figure 3A), quantifiable by an increase in the ratio of 10–100 Hz to 1–10 Hz power ( p < 0.02, Wilcoxon signed-rank test, Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…We first examined if activation of the LC-NE neurons using electrical microstimulation would alter cortical arousal by shifting the power spectrum of cortical EEG, as had been previously shown using pharmacological compounds (Berridge and Foote, 1991; Steriade et al, 1993; Vazey and Aston-Jones, 2014) and photostimulation (Li et al, 2016). Consistent with previous work, brief electrical microstimulation (50 Hz, 6 biphasic current pulses, 200 ”s per phase, 60 or 120 ”A amplitude) of the LC induced the EEG power spectrum to shift towards higher frequencies (Figure 3A), quantifiable by an increase in the ratio of 10–100 Hz to 1–10 Hz power ( p < 0.02, Wilcoxon signed-rank test, Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…For example, pathway specific manipulation may be achieved using two vectors by infusing a retrograde canine adenovirus-2 into a target region (e.g., mPFC) to deliver Cre-recombinase and an adeno-associated virus carrying a designer receptor into a target region that projects to the first region (e.g., VH) (Boender et al, 2014). Likewise, optogenetics also allows for similar pathway specific manipulation (Li et al, 2016; Walsh et al, 2012). The temporal resolution provided by optogenetics may be particularly useful given the defined CS-US onset-offset parameters of trace conditioning.…”
Section: Future Studiesmentioning
confidence: 99%
“…Recent optogenetic studies have shown that focal activation of the LC, whose major inputs are from the PFC, amygdala, PAG and dorsal noradrenergic bundle, may be either pro- or anti-nociceptive, suggestive of different neuron subgroups within the LC (Hickey et al, 2014). Consistent with this, recently Li et al (2016), used a canine adenoviral vector expressing channelrhodopsin2 to target ponto-spinal NE neurons, and found a subset of ventral LC neurons with spinal projections that is likely involved in the regulation of nociception. Interestingly, this subgroup of LC neurons had lower average firing rate than other noradrenergic neurons of the LC.…”
Section: Discussionmentioning
confidence: 68%
“…Most evidence available supports the PAG as a useful stimulation target (Pereira and Aziz, 2014). In addition to ascending somatosensory projections, the PAG receives significant inputs from the prefrontal cortex (PFC) and amygdala and then projects to nucleus raphe magnus (NRM) and locus coeruleus (LC) in the midbrain and dorsal horn neurons in the spinal cord (Van Bockstaele et al, 1991; Li et al, 2016). Recent case series on DBS for chronic neuropathic pain, which have utilized superior targeting methods compared to earlier studies and multi-day trials with an externalized electrode prior to final implantation, suggest clinically-relevant improvements of pain symptoms in 67%–83% of patients with heterogeneous types of pain (Boccard et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation